Comparison of CPF approved and non-CPF approved unit trusts returns. - Chan, Vivian Wai Man. (2008)
We investigated the returns between CPF and non-CPF approved unit trusts. We did not find any significant differences between their returns. Thus it might not be necessary for CPF Board to make such distinction.